Investigation of discharge characteristics of a tri-generative system based on advanced adiabatic compressed air energy storage. (15th November 2018) - Han, Zhonghe; Guo, Senchuang
Highlights: Four performance indexes of constant-sliding mode are the best. Cooling capacity of constant-sliding mode is the strongest. The exergy destruction of air storage chamber is the largest. Three modes have similar variation tendencies of parameters of air storage chamber. Abstract: The tri-generative system based on advanced adiabatic compressed air energy storage can simultaneously provide cooling energy, heating energy and mechanical energy. In order to study the discharge characteristics, three operation modes of expanders, which contain constant pressure, constant-sliding and sliding pressure, are proposed in this paper. By utilizing the numerical simulation method, the performance difference of three modes is compared with each other. The results show that four performance indexes of constant-sliding mode are all the biggest, which are respectively cycle efficiency 40.55%, thermal efficiency 80.06%, exergy efficiency 48.45% and exergy density 4.071 × 10 6  J·m −3, and cooling capacity of it is also the strongest, 8.386 × 10 9  J, among the three operation modes. Air storage chamber has the largest exergy destruction. Operation process of air storage chamber is similar for three operation modes. Meanwhile, the effects of heat exchanger effectiveness, ambient pressure and air storage chamber model on system performance are also investigated.